Economic-financial evaluation of a beef cattle breeding system in the dairy region of minas gerais - Ferreira, Robson Leandro; Carvalho, Carlos Augusto Brandão de; Peres, Afonso Aurélio de Carvalho; Souza, Paulo Marcelo de; Barbero, Rondineli Pavezzi [UNESP]; Garcia, Felipe Zumkeller; Xavier, Deygiane Theodoro (My University, 2021)
The objective was to determine production costs, economic efficiency indicators and return on investment of a beef cattle breeding system. Electronic spreadsheets were prepared from January 2012 to December 2018 for cost analysis and determination of economic efficiency indicators (gross margin, net margin, result, profitability and profitability), in addition to the cash flow for obtainment economic profitability indicators: net present value (NPV), internal rate of return (IRR) and payback. The most representative items in the total cost were: hired labor (23.6%), family labor (19.7%), opportunity costs (13.6%) and depreciation (12.9%). The result, profit and profitability indicators were negative from 2012 to 2015, and positive in the following years, when calculated without including the balance of equity variation. The production system was economically viable, with a discount rate of 2% p.y., and the profitability without land appreciation was attractive for investment. The recovery of invested capital takes place in the medium term. The sale price of animals and investment in land caused the greatest impacts on economic indicators.
Keywords: Economic indicators of profitability; Economic-financial viability; Production cost